O eclipse de existência: figurações da velhice em contos de Moreira Campos - Alexandre, Aurélia Bento (2016)
This study analyzes the construction of the discourse on old age in Moreira Campos’ prose (1914- 1994). In order to achieve our goal, we chose the short stories: “As velhas”, “A antiga fada”, “Os fantasmas”, “O grande medo” e “Os pesados lagartos”, which are present at the book O puxador de terço (1969). In the narratives of Moreira Campos, older characters are represented as lonely people facing real battles, sometimes even with themselves, to keep a dialogue with the surrounding world whether is their family or the social environment and this analysis focuses on this aspect. Therefore, we propose to observe the way old age has gained a figurative character in literary narratives, particularly in Moreira Campos’ short story fiction, trying to notice what makes it singular and different when it comes to old people representation in modern literature. This research comprises the social context in which the books are placed, promoting a dialogue that shows how the social and historical life are set in the alluded short stories. Literatura e Sociedade (1967), by Candido, supports the discussion and establishment of the literary text relation with the social reality. Regarding the discussion that we bring about modernity, the ideas of Berman (2007), in Tudo que é sólido desmancha no ar, are extremely important. Old age discussions have as theoretical support the thought of Beauvoir (1990), Secco (1994) and Bosi (1994). The dissertation shows that the narratives analyzed, including old age in its historical and social dimension, highlight some exclusive procedures dispensed to old people in capitalist modern society: devaluation, abandonment and absence of projects to reintegrate the elderly to society making them feel useful.